Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.chemrestox.5b00513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Twelve Germline Missense Variations on DNA Lesion and G-Quadruplex Bypass Activities of Human DNA Polymerase REV1

Abstract: The Y-family DNA polymerase REV1 is involved in replicative bypass of damaged DNA and G-quadruplex (G4) DNA. In addition to a scaffolding role in the replicative bypass, REV1 acts in a catalytic role as a deoxycytidyl transferase opposite some replication stall sites, e.g. apurinic/apyrimidinic (AP) sites, N2-guanyl lesions, and G4 sites. We characterized the biochemical properties of 12 reported germline missense variants of human REV1, including the N373S variant associated with high risk of cervical cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Further characterization of the in vivo functional consequences of these and other as-yet unidentified POLK gene variations would contribute to a better understanding of the roles of human pol κ variants in individual’s propensity for mutations and their possible clinical implications, e.g., individual differences in cancer risks and treatment responses, with regard to specific genotoxic agents, in human populations. Our present and previous findings on Y-family pols 1618 also suggest that there likely exist a considerable number of (albeit mostly rare) dysfunctional genetic variations for Y-family pols in human population. Our growing knowledge about functional genetic variations of human TLS pols might provide some insight into understanding the complex genetic basis of cancer risks related to specific carcinogens.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further characterization of the in vivo functional consequences of these and other as-yet unidentified POLK gene variations would contribute to a better understanding of the roles of human pol κ variants in individual’s propensity for mutations and their possible clinical implications, e.g., individual differences in cancer risks and treatment responses, with regard to specific genotoxic agents, in human populations. Our present and previous findings on Y-family pols 1618 also suggest that there likely exist a considerable number of (albeit mostly rare) dysfunctional genetic variations for Y-family pols in human population. Our growing knowledge about functional genetic variations of human TLS pols might provide some insight into understanding the complex genetic basis of cancer risks related to specific carcinogens.…”
Section: Discussionsupporting
confidence: 81%
“…1, 14, 15 In this respect, it can be speculated that the cellular capacity for faithful replication in the presence of DNA damage may be an important determinant for genome maintenance, and thus the functional and genetic alterations of TLS pols might modify overall mutation consequences (e.g., frequency and spectrum) of DNA damage induced by carcinogens in cells, potentially contributing to mutation or cancer susceptibility in the affected individuals. Our recent studies reveal that a substantial number of human natural germline genetic variants of TLS pols ι, κ, and REV1 are catalytically altered (either impaired or enhanced in TLS activity), 1618 implying their potential for individual alterations in TLS capacity and mutation risk to certain genotoxic carcinogens in genetically predisposed individuals.…”
Section: Introductionmentioning
confidence: 98%
“…It is also likely that Rev1 functions in conjunction with DNA helicases that help unwind the G4 structure [98], a suggestion requiring further biochemical studies. A study by Yeom et al suggested that certain germline missense variations in Rev1 may either inhibit or enhance the ability of Rev1 to bypass G4 motifs, thereby affecting an individual’s susceptibility toward carcinogenesis [108], a finding which warrants further study of Rev 1 as a potential drug target.…”
Section: Bypass Of G4 By Translesion Dna Polymerasesmentioning
confidence: 99%
“…Several studies have documented altered expression and function of TLS polymerases and of their proximal activator RAD18 in cancer. For example a steady state kinetic analyses of REV1 proteins harboring different polymorphisms (including variants associated with cancer) revealed moderate or slight effects on biochemical activities (such as kcat/Km for dCTP insertion, binding affinities to DNA substrates harboring various lesions) when compared with wild-type REV1 [ 37 ]. Therefore, it is plausible that germline missense REV1 variations affect cancer susceptibility by modifying the fidelity and capacity for replication on undamaged and damaged DNA templates.…”
Section: Introductionmentioning
confidence: 99%